Revealing the identity of Josa chazaliae (Simon, 1897) (Araneae: Anyphaenidae): new species and the highest altitude record for a spider in South America - Martínez, Leonel; Kochalka, John A.; Cabra-Garcia, Jimmy; Ramírez, Martin (Zootaxa, 2025)
We examined the type series of Josa chazaliae (Simon, 1897) from Sierra Nevada de Santa Marta, Colombia, composed of three females of two different species. Herein, we propose a lectotype for Josa chazaliae, redescribe the female, and describe the male of this species for the first time. A new species, Josa samaria sp. nov., is proposed based on a female paralectotype of Josa chazaliae. Three additional species, all based on both sexes are described: Josa nadineae sp. nov., Josa berlandi sp. nov., and Josa olimpica sp. nov. All species studied in this work occur in Sierra Nevada de Santa Marta, the highest coastal mountain system in the world. We compared our geographical data with the records of spiders available in GBIF, the MACN-Ar database along with unpublished records for the described Josa species. The results indicate that the presence of Josa olimpica at altitudes of at least 5500 masl represents the highest record for a spider in South America, and apparently the highest record for any spider in the Western Hemisphere.